Role of Attention in the Regulation of Fear and Anxiety - White, Lauren K. (Dev Neurosci, 2009)
Emotion regulation makes use of specific aspects of attention and executive functions that are critical for the development of adaptive social functioning, and perturbations in these processes can result in maladaptive behavior and psychopathology. Both involuntary and voluntary attention processes have been examined at both the behavioral and the neural levels and are implicated in the maintenance of fearful or anxious behaviors. However, relatively little is known about how these attention processes come to influence emotional behavior across development. The current review summarizes the extant literature on the links between voluntary and involuntary attention processes and the role that these attention processes have in the etiology, maintenance, and regulation of anxious behavior.